Processo de institucionalização: um estudo da Lei Geral da Micro e Pequena Empresa - Moreira, Cleverson Bayer (2021)
This work used sociological-based institutional theory to reveal all the steps taken by the authorities of a municipality of the interior of the state of Paraná for the implementation of the Micro and Small Business Law. The chosen methodology was observed by no participant and semi-structured interviews with the leaders of the municipality. To economic and social political concern, we areworking onthepositionthat we takeis thattheinstitutional theory is not unique to culture and behavior that is individual or organizational. It is intended to understand how the Micro andSmall Business Laws were implemented in this municipality from the initial discussions and the definitive operationalization. We emphasize that the investigationoccupiedasufficienttimeperiodtoanswerthepertinentquestionsandthattwo mainstream investigators show or disagreewith institutionalized politicalquestions such as bureaucracy and delinquency pertaining to culture and behavior. o individual and organizational behavior in this context, not over the years institutes built while altering the social order. As either the process is constant, or the time span of the investigation is presented as limiting, bearing or that we can attach to the moment or moment of this mismatch between institution and behavior.